2020
DOI: 10.1007/s12325-020-01243-y
|View full text |Cite
|
Sign up to set email alerts
|

An Economic Evaluation of Voretigene Neparvovec for the Treatment of Biallelic RPE65-Mediated Inherited Retinal Dystrophies in the UK

Abstract: Introduction: Voretigene neparvovec (VN) is a gene therapy and the first approved pharmacological treatment for biallelic RPE65-mediated inherited retinal dystrophies (IRD), a rare condition that starts in early life and causes vision to progressively deteriorate towards complete blindness. In a phase III trial, treatment with VN significantly improved functional vision and visual function, and in October 2019 the National Institute for Health and Care Excellence (NICE) Highly Specialised Technologies Enhanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 23 publications
2
23
0
Order By: Relevance
“…A decreasing treatment effect is mainly associated with a loss of QALYs and higher overall costs, primarily driven by the increase of indirect costs. This is consistent with the results of Johnson et al 10 and Viriato et al, 11 where the treatment effect was also identified as the largest individual driver. We expect that estimation of treatment effect duration may be one of the main factors for cost-utility analyses not only in VN, but also in many future gene therapies.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…A decreasing treatment effect is mainly associated with a loss of QALYs and higher overall costs, primarily driven by the increase of indirect costs. This is consistent with the results of Johnson et al 10 and Viriato et al, 11 where the treatment effect was also identified as the largest individual driver. We expect that estimation of treatment effect duration may be one of the main factors for cost-utility analyses not only in VN, but also in many future gene therapies.…”
Section: Discussionsupporting
confidence: 92%
“…Because indirect cost data vary greatly between different countries, a direct comparison between studies is not possible. However, additional QALYs gained and ICURs of our results point in the same direction as the 2020 study by Viriato et al, 11 who estimated VN to be cost effective for the UK and assumed a gain of 6.4 QALYs. This study confirms our finding that substantial QALY gains can be attributed to the therapy when its effects are modeled with a life time perspective.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations